A Confucian View of Informed Consent and the Issue of Vaccination - Fan, Ruiping (Studia Bioethica, 2019)
To explore a Confucian view of informed consent, one will first need to understand the general moral nature of Confucian tradition. Confucian tradition carries a virtue-based and virtue-oriented moral system. It takes the concept of virtue, rather than the concept of individual right, liberty, or equality, as the ground of morality[i]. In other words, Confucianism would link human dignity with virtue, not with individual right, liberty, or equality[ii].